Language and trade: the (new) route of portuguese in the 21st century - Albuquerque, Alexandra (2012)
Globalisation has eliminated frontiers and in the case of Europe helped the crossing of borders and changed forever the concept of social (and I would also say individual) geography: the rest of the world is out there; we can pretend not to see it, but we cannot avoid it. Moreover, Europe is undergoing a serious crisis, also economic, and new markets and business partners are welcome. In this context, cultural bonds like a common language can open new investment paths and give rise to successful stories. In this paper we intend to present an example of how low linguistic distance can lead to good business, even if a) in the internationalization process of the companies’ language is often forgotten as a management element and b) consumers of language products (like User Guides) are also not stimulating investment in language by the companies. Through the results of 2 studies carried out in 2010 and 2011 we will show how a pluricentric language like Portuguese is managed in multinational companies (MC) and Small and medium Enterprises (SMEs). The second study is based on an online survey questioning the effectiveness, efficiency and general quality of User Guides and the reaction of consumers to language. Results show that although playing a role in the internationalization process of companies in the same linguistic space, language is opportunistically used. On the other hand, Portuguese and Brazilian consumers show a very functional perception of the Portuguese language...